Effects of Tooth Surface Crack Propagation on Meshing Stiffness and Vibration Characteristic of Spur Gear System - Lan-tao Yang; Yi-min Shao; Wei-wei Jiang; Lu-ke Zhang; Li-ming Wang; Jin Xu (Applied Sciences, 2021)
Tooth surface cracks are considered as the early stage of the development of tooth surface spalling failure. Understanding the excitation mechanism of surface cracks has a great significance in the early diagnosis of spalling faults. However, there are few studies on the dynamic modelling of surface cracks, and the influence mechanism of surface cracking on the dynamic characteristics of a gear system is also not yet clear during its propagation process. Thus, an analytical calculation model of the meshing stiffness of gear with tooth surface crack is developed. Then, a dynamic model of a spur gear system with six degrees of freedom (DOF) is established based on the proposed surface crack calculation model. The effects of surface crack propagation on the meshing stiffness and dynamic characteristics of gear system are investigated. The results show that the side frequencies of dynamic transmission error (DTE) are more sensitive than those of the acceleration responses during the surface crack propagation, which is more favorable to the surface crack fault diagnosis. Compared to the traditional spalling fault model, the proposed model can accurately characterize the dynamic characteristics of a gear system with the early spalling defect.